INTERVENTION PROCEDURE IN DRAWING CLASSES FOR NON-ART UNIVERSITY STUDENTS: THE IMPACT OF ASSIGNMENT REDESIGN ON STUDENTS’ PERFORMANCE - Curcic, Dimitrije (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Drawing allows students to actively engage with the topic they are learning, as opposed to only taking knowledge passively (Abdullah et.al., 2023). The endeavor to teach fundamental freehand drawing techniques to non-art university students poses distinct challenges necessitating the adaptation of specific instructional methodologies. This study investigates the impact of assignment design as a part of instructional methods in a freehand drawing course tailored for non-art students and its consequent effects on student performance. Employing a multifaceted data collection methodology involving intervention, post-intervention analysis, and self-reflection questionnaires about students’ perceptions of the learning process, the study seeks to elucidate which interventions in instructional procedure are efficient in improving students’ overall performance. The study cohort comprises 63 second-year students drawn from diverse faculties at Prince of Songkla University in Hat Yai, Thailand, encompassing eleven students from the first semester and fifty-two from the second semester of the academic year 2023. Through visual analysis post-intervention, informed by standardized rubric score criteria, the findings evince a significant correlation between assignment themes and student performance. Furthermore, discernible enhancements across various assignment categories suggest a marked improvement in learning outcomes attributable to the redesigned assignments implemented in the second semester compared to their counterparts in the first semester of the academic year 2023.